Long term outcome of tibial adamantinoma: a case report and literature review - Benabdallah, Otman; Benbrahim, Youssef El Andaloussi; Bensouda, Ahmed; Benabdallah , Rania (International Journal of Research in Orthopaedics, 2025)
Adamantinoma is a rare malignant bone tumor that typically occurs in the tibia but can also occur in the jaw, forearm, hands, or feet. It commonly affects young adults between 20 and 40 years. It accounts for less than 1% of primary bone tumors. It is a slow growing tumor and often indolent but generally symptoms are persistent pain in the affected area, localized swelling, tibial bowing deformity and pathological fracture which occurs acutely. the diagnosis is based on imaging and a necessary biopsy to confirm the diagnosis, showing nests of epithelial-like cells in a fibrous stroma. The treatment consists of surgical resection and recurrence can be problematic and may occur even decades after initial treatment. Here, we report one case of tibial adamantinoma with atypical treatment and long-term evolution greater than 24 years and with no recurrence.